Dampak Kehadiran Pasar Modern Maju Bersama Terhadap Pendapatan Pedagang Pasar Tradisional MMTC - Fitri Handayani; Khairul Saleh; Muhammad Fadly Abdina (Universitas Medan Area, 2022)
The market is a place where transactions of goods are carried out by more than one seller and buyer. Traditional markets and modern markets are often located in one area close together. This will have an impact on traditional market traders. The impact of the existence of modern markets on traditional markets is in terms of a decrease in the income of traditional traders. This study aims to determine the impact of the presence of the Maju Bersama modern market on the income of MMTC traditional market traders. This research was carried out at the MMTC market, Percut Sei Tuan district in August 2021 with a total sample of 30 traditional market traders at MMTC who were taken by purposive sampling method. While the data collection method using questionnaires and interviews. The results showed that there was an influence on the income of traditional market traders at MMTC Market, Percut Sei Tuan District with the existence of the Maju Bersama modern market. The income of traditional market traders after the presence of the Maju Bersama modern market resulted in a decrease in income of 7.51%. The average income of traditional traders before the Maju Bersama modern market was Rp 2,063,333, and after the Maju Bersama modern market it was Rp 1,908,333. Sales of traditional traders after the existence of the Maju Bersama modern market decreased by 11.26%. The decline in sales of traditional traders has more impact on fruit sales, while buyers still choose to buy vegetables at traditional traders.